Climate Risk Management in Agricultural Extension (CRMAE) Curriculum: Training of Trainers for Senegal’s Agricultural Extension System - Grossi, Amanda; Braun, Melody; Hansen, James; Trzaska, Sylwia; List, Geneva; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A nine-day training of trainers (ToT) workshop on the Climate Risk Management in Agricultural Extension (CRMAE) curriculum was convened from March 6-15, 2023, in Saly, Senegal with the country’s main extension and advisory service (EAS) providers from both the public and private sectors. The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought these EAS providers together to train them on a new co-produced and competency-based curriculum to build foundational knowledge and skills to manage climate risk in agriculture. In particular, the curriculum aims to help EAS providers to take advantage of best-available and location-specific climate information products and tools in Senegal, including those freely available and accessible online through the National Agency for Civil Aviation and Meteorology (ANACIM) to better plan for, manage, and respond to a changing and varying climate.